PenetaPan Hadis sebagai HujjaH dalam menjawab isu-isu KontemPorer (studi Pada bahtsul masail muktamar nu Ke-33 tahun 2015) - Armita, Pipin (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2017)
Hadis is one of reference to solve problems that arise in contemporary societyissues. Likewise conducted by Nahdhatul Ulama (NU) on Bahtsul MasailMuktamar NU 33th 2015. Th interesting thing is how does NU positioninghadis as a proof (hujjah) to deciding religion contamporary issues in theBahtsul Masail. So, this paper aims to how determination Hadith as one ofproofin Bahtsul Masail on Muktamar NU 33th 2015 and what methodsis used by NU to determine that hadith as a proof. Ths reseach usingarchaeological approach to analyse the problems what carried by Foucalton power and knowledge relation theory. Base on this theory, truth must beconceived as a system ofprocedures to regulate the production, regulation,distribution, circulation, and operation statements. As the result, authorfound that on Bahtsul Masail Muktamar NU 33th 2015 there are 13themes that include hadis as a proof either either directly through the bookofHadith or Fiqh book, book oftafsir, and others.